Eksistensi Kepemimpinan Pemerintahan Diantara Krisis Pandemi Covid-19 Dan Digital Disruption - Iwan Kurniawan (UIR Press, 2022)
Leadership in times of crisis has a vital role, therefore the decisions chosen can improve the situation or make things worse. This article looks at the phenomenon of leadership from two things, namely during the pandemic and the momentum of digital disruption. These two things are closely related and occur simultaneously. No less important than adapting to a new form is conformity to the conditions needed to become something new that people eventually become accustomed to. This article uses a variety of primary and secondary data as well as field facts that have occurred in Indonesia for the past three years and uses a qualitative descriptive method, this method is considered appropriate to explain, describe and analyze this discussion.